Prinsip Prinsip dan Kaidah Hukum Islam: Tidak Picik, Tidak Memberatkan, Diterapkan Secara Bertahap, Memperhatikan Kemaslahatan Manusia dan Mewujudkan Keadilan: Penelitian - Nazmi Septrina; Salma Salma; Muchlis Bahar (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The principles and rules of Islamic law are essentially established to realize human welfare, maintain justice, and uphold universal humanitarian values. Islamic law is not narrow-minded and rigid, but rather flexible, adaptive, and considers the social conditions of society. The principle of